PENGARUH SALINITAS TERHADAP DAYA TETAS TELUR IKAN BAUNG (Hemibagrus nemurus Blkr.) - Yanal Hadid; Mochamad Syaifudin; Mohamad Amin (Jurnal Akuakultur Rawa Indonesia, 2014)
ABSTRACT The purpose of the study was to know the best salinity of eggs hatching period, the hatching percentage, the hatching rate, the percentage of normal larva and survival rate of baung fish larva (Hemibagrus nemurus Blkr.) until it 2 days age.   This research was conducted at Balai Benih Ikan of Gandus sub-district, Palembang, South Sumatra Province in February 2008. This research used the Complete Random Design with four different salinity treatments as like S0 (control), S1 (2 ppt), S2 (4 ppt), and S3 (6 ppt) by each three replications. Parameter observed the hatching period, the hatching percentage, the hatching rate, the percentage of normal larva, the survival rate of larva 2 days age, and  water quality. This result of the research showed that the salinity influenced evidently on the hatching capability of Baung Fish Eggs. The salinity 6 ppt had fastest time for the hatching period with of hatching time was 21.73 hours then hatch entirely after 29 hours. The best salinity for the hatching percentage (85,33%) and the hatching rate  (21.37 fish per hour) was 2 ppt. The control had the highest value (95.05%) for the percentage of normal larva. The salinity of 2 ppt had the highest value (82.59%) for the life of larva on age of 2 days. This measure of water quality is temperature (27.5 oC-28 oC), pH (7.00-7.12), DO (6.0-6.5 mg.L-1), and NH3 (0.05-0.09 mg.L-1).   Keywords: Hemibargus nemurus, salinity, egg hatching percentage